Development and Validation of Laboratory Manual in Life Science for Grade 11 Senior High School: An Input to Instructional Material Development - Renniza Diola (Journal of Elementary and Secondary School, 2023)
The primary purpose of this study was to develop and validate a laboratory manual in Life Science intended for Grade 11 Senior High School using the first three stages of the ADDIE Model. A descriptive evaluative method of research was utilized in gathering and analyzing data. Fifty (50) Science experts of the institution and experts from National High School in the Second and Third District of Laguna were selected as respondents using purposive sampling. A questionnaire checklist using Likert Scale was adopted to determine the mean acceptability level of the teacher-respondents in terms of the manual’s content, organization and presentation, language and style, accuracy, up-to-datedness, and usefulness. Findings revealed that experts strongly agreed that the developed laboratory manual has sufficient content and technical qualities, making it an acceptable supplementary material in teaching life science. Meanwhile, the average weighted means for each category range from 4.27 to 4.46, which is interpreted as highly acceptable. These results suggest that the laboratory manual is well-designed, organized, and written effectively and accurately. The findings suggest that the manual is useful and provides a valuable resource for teaching Life Science.